Pelatihan dan Pendampingan Pembuatan Bahan Ajar Digital Berbasis Artificial Intelligence (AI) - Syahfitri, Jayanti; Muntahanah, Muntahanah; Irwandi, Irwandi (STMIK Royal, 2024)
SD Negeri 140 Seluma has a relatively large number of human resources, both teachers and students. However, this is also a challenge for partner schools where some of the problems that are often faced are the lack of knowledge and competence of teachers in providing digital teaching materials to facilitate differentiated learning, which impacts the formation of students' character optimally. This training and mentoring is an effort to improve teacher knowledge and competence in providing teaching materials. This activity involved 30 teachers through two methods, namely: socialization, training and mentoring (the practice of making AI-based learning videos). The activity results showed that all participants experienced an increase in understanding related to the concept of digital teaching materials and increased competence in making AI-based learning videos. This is evidenced by the products that have been produced by the training participants. Keywords: artificial intelligence; digital teaching materials; training; accompaniment SD Negeri 140 Seluma memiliki SDM dengan jumlah yang relatif banyak baik guru maupun peserta didik. Namun, hal ini sekaligus menjadi tantangan bagi sekolah SD Negeri 140 Seluma dimana beberapa permasalahan yang seringkali dihadapi yaitu masih minimnya pengetahuan dan kompetensi guru dalam menyediakan bahan ajar digital untuk memfasilitasi pembelajaran berdiferensiasi, sehingga berdampak pada pembentukan karakter peserta didik secara optimal. Pelatihan dan pendampingan ini merupakan upaya yang dilakukan untuk meningkatkan pengetahuan dan kompetensi guru dalam menyediakan bahan ajar. Kegiatan ini melibatkan 30 orang guru melalui dua metode yaitu: sosialisasi, pelatihan dan pendampingan (praktik pembuatan video pembelajaran berbasis AI). Hasil kegiatan menunjukkan peningkatan pemahaman dan keterampilan peserta dalam memproduksi video pembelajaran berbasis AI, yang dibuktikan melalui produk video yang dihasilkan. Kata kunci: artificial Intelligence; bahan ajar digital; pelatihan; pendampingan